(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Although there has been an increase in the discussion of both work interferences with family and workplace deviance at the workplace, it is still obscure how these two substantial concepts are connected. A review of the existing research demonstrates an affiliation between work interference with family and workplace deviance. The relationship between these two important dimensions was discovered and defined by many studies using diverse variables such as mediating and moderating variables. Stress, burnout, emotional exhaustion, perceived organizational support, and work-family resentment are mediating variables that several researchers have used, whereas gender, transformational and transactional leadership and after-work technology moderated the association. The linkage between two significant constructs was clarified by this thorough literature analysis, which also offered potential directions for further study.